Fact sheets from the Sir Norman Chester Centre for Football Research
Fact sheets from the Sir Norman Chester Centre for Football Research 1. Football and Football Hooliganism (35K + 16K images) 2. Football After Taylor (22K + 18K images) 3. Why Support Football? (14K + 7K images) 4. Black Footballers in Britain (30K) 5. Women and Football (25K + 20K images) 6. Racism and Football (31K) 7. Fan Power and Democracy (46K + 12K images) 8. British Football On Television (unavailable at present) 9. A History of Female Football Fans (24K + 10K images)